Molecular Responses to Cadmium Exposure in Two Contrasting Durum Wheat Genotypes - Sabella, Erika (Int J Mol Sci, 2021)
Cadmium is a heavy metal that can be easily accumulated in durum wheat kernels and enter the human food chain. Two near-isogenic lines (NILs) with contrasting cadmium accumulation in grains, High-Cd or Low-Cd (H-Cd NIL and L-Cd NIL, respectively), were used to understand the Cd accumulation and transport mechanisms in durum wheat roots. Plants were cultivated in hydroponic solution, and cadmium concentrations in roots, shoots and grains were quantified. To evaluate the molecular mechanism activated in the two NILs, the transcriptomes of roots were analyzed. The observed response is complex and involves many genes and molecular mechanisms. We found that the gene sequences of two basic helix–loop–helix (bHLH) transcription factors (bHLH29 and bHLH38) differ between the two genotypes. In addition, the transporter Heavy Metal Tolerance 1 (HMT-1) is expressed only in the low-Cd genotype and many peroxidase genes are up-regulated only in the L-Cd NIL, suggesting ROS scavenging and root lignification as active responses to cadmium presence. Finally, we hypothesize that some aquaporins could enhance the Cd translocation from roots to shoots. The response to cadmium in durum wheat is therefore extremely complex and involves transcription factors, chelators, heavy metal transporters, peroxidases and aquaporins. All these new findings could help to elucidate the cadmium tolerance in wheat and address future breeding programs.